Denaturing Gradient Gel Electrophoresis (DGGE) in microbial ecology: insights from freshwaters - Duarte, Sofia Alexandra Ferreira (2012)
The Portuguese Foundation for the Science and Technology supported this work (PTDC/AAC-AMB/113746/2009) and S. Duarte (SFRH/BPD/47574/2008).